A Proposed Conceptual Framework for K-12 STEM Master Teacher (STEMMaTe) Development - Rebecca Hite; Jeff Milbourne (MDPI AG, 2018)
Recent reports from federal agencies and legislation call for explicit avenues to incorporate K⁻12 STEM master teacher voice into the policy space. National initiatives, federal legislation, and teacher recognition programs have sought to identify K⁻12 STEM master teachers and harness their potential. These efforts warrant a conceptual framework to quantify attributes of K⁻12 STEM master teachers, to foster pathways for the development of current and future leaders. Using a sample of 10 individuals from two extant programs of K⁻12 STEM master teachers (Albert Einstein Distinguished Educator Fellowship and Presidential Awards for Excellence in Mathematics and Science Teaching), data from their career trajectories (sourced from Curriculum Vitae) were sequenced to construct and confirm the STEM Master Teacher (STEMMaTe) conceptual framework. This framework may be used to guide programmatic development to increase national capacity for K⁻12 STEM master teachers. Recommendations are discussed for the creation of pathways to develop STEM master teachers and increase their participation in the broader education system.